Subscription Economy: The Future of Customer-Centric Marketing - Elanda, Yochi; Rizki, Ainur; Masruchan (SAFE-Network, 2024)
This study examines the intricate interplay between subscription models, personalized marketing strategies, customer engagement, and satisfaction within the context of PT. Socfin Indonesia, an agricultural company. Utilizing a quantitative research design with a sample of 100 consumers, the study employs path analysis to analyze direct and indirect effects. The findings highlight significant direct effects of subscription models and personalized marketing strategies on customer engagement and satisfaction. Moreover, the study unveils notable indirect effects, indicating that these factors influence satisfaction through their impact on engagement. The results underscore the importance of customer-centric approaches, emphasizing the pivotal role of fostering deeper engagement to enhance satisfaction and loyalty. Consequently, PT. Socfin Indonesia is encouraged to invest in optimizing subscription models and tailoring marketing strategies to individual preferences, thus ensuring sustained success in the agricultural sector.